Periprocedural analgesia and sedation in air enema reduction for intussusception: A retrospective Australian cohort study. (9th September 2020) - Yeoh, Kenny; Palmer, Greta M; Teague, Warwick J; Shavit, Itay; Babl, Franz E
Abstract : Aim: Periprocedural analgesia or sedation for air enema reduction (AER) of intussusception is a matter of debate. We set out to review Australian periprocedural pain management in AER. Methods: Retrospective electronic medical record review of emergency department presentations of intussusception at an Australian children's hospital over 2 years for periprocedural analgesia and sedation and short‐term outcomes. Results: A total of 73 patients (mean age 23 months) had ultrasound‐confirmed intussusception. Prior to AER, analgesia was administered to 61 of 73 (83.5%) patients. Opioids were administered in 48 of 73 (65.8%) and 8 of 73 (11.0%) received sedation. Thirteen of 73 (17.8%, 95% confidence interval 9.0–26.6) had spontaneously reduced; 60/73 that underwent primary AER had successful reduction in 54 (90.0%, 95% confidence interval 82.4–97.6). A total of seven patients required surgery. No AER attempts were complicated by bowel perforation. Conclusion: The use of periprocedural analgesia for AER in this Australian series was common, whilst sedation use was infrequent. No perforations occurred.